Flexible Credit Line-Operational Guidance Note. (Policy Papers; Policy Paper ;, 2012)
The Flexible Credit Line (FCL) was introduced as part of a package of reforms to the Fund's lending facilities in March 2009 and its design was further refined in August 2010. The following provides operational guidance and further background information on the FCL. SPR (the Emerging Markets Division), FIN, and LEG stand ready to clarify any further questions departments may have on the FCL or other aspects of the reforms to lending and conditionality.